Pengaruh Kemudahan Penggunaan Mobile Banking dan Harga Barang Terhadap Perilaku Konsumtif Mahasiswa Pengguna Online Shop - Hasyim, Hasyim; Situmorang, Elsa Aurel Agustine; Sinurat, Penus Leonard Roningsih; Batu, Selfiana Lumban (Journal of Management Accounting, Tax and Production, 2025)
This study aims to examine the impact of mobile banking ease of use and product pricing on the consumptive behavior of students who use online shopping platforms. With advancements in technology, particularly mobile banking, students can easily perform online transactions, which may influence their consumption behavior. The prices offered by e-commerce platforms also play a significant role in encouraging purchases. This research adopts a quantitative approach using multiple linear regression analysis on data from 30 student respondents from the 2022 Economic Education program at Universitas Negeri Medan. The results show that both mobile banking ease of use and product pricing have a significant influence, both partially and simultaneously, on students' consumptive behavior. These findings provide valuable insights into how technology and pricing strategies affect consumption habits among students.